2016
DOI: 10.1051/0004-6361/201527688
|View full text |Cite
|
Sign up to set email alerts
|

Aλ3 mm and 1 mm line survey toward the yellow hypergiant IRC +10420

Abstract: Aims-Our knowledge of the chemical properties of the circumstellar ejecta of the most massive evolved stars is particularly poor. We aim to study the chemical characteristics of the prototypical yellow hypergiant star, IRC +10420. For this purpose, we obtained full line surveys at 1 and 3 mm atmospheric windows.Methods-We have identified 106 molecular emission lines from 22 molecular species. Approximately half of the molecules detected are N-bearing species, in particular HCN, HNC, CN, NO, NS, PN, and N 2 H +… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…The SO (1 × 10 −6 ), SiO (5 × 10 −6 ), and CS (1 × 10 −6 ; after correcting the 13 CS abundance by the estimated 12 C/ 13 C ≈ 10) abundances all lie in the range reported for AGB CSEs (Danilovich et al 2016;Schöier et al 2013;Velilla Prieto et al 2017), while the H 2 CO abundance (2 × 10 −6 ; assuming an orthoto-para ratio of 3) is about an order of magnitude higher than in IK Tau (Velilla Prieto et al 2017). CH 3 OH has an estimated abundance of 3 × 10 −6 (assuming an E-to-A ratio of 1), almost two orders of magnitude higher than towards the supergiant IRC+10420 (Quintana-Lacaci et al 2016). However, the large distance between HD 101584 and the EVS (3 × 10 17 cm) combined with a reasonable expansion velocity of the AGB wind (15 km s −1 ) indicate a time scale of ≈6500 yr.…”
Section: Chemistrysupporting
confidence: 50%
“…The SO (1 × 10 −6 ), SiO (5 × 10 −6 ), and CS (1 × 10 −6 ; after correcting the 13 CS abundance by the estimated 12 C/ 13 C ≈ 10) abundances all lie in the range reported for AGB CSEs (Danilovich et al 2016;Schöier et al 2013;Velilla Prieto et al 2017), while the H 2 CO abundance (2 × 10 −6 ; assuming an orthoto-para ratio of 3) is about an order of magnitude higher than in IK Tau (Velilla Prieto et al 2017). CH 3 OH has an estimated abundance of 3 × 10 −6 (assuming an E-to-A ratio of 1), almost two orders of magnitude higher than towards the supergiant IRC+10420 (Quintana-Lacaci et al 2016). However, the large distance between HD 101584 and the EVS (3 × 10 17 cm) combined with a reasonable expansion velocity of the AGB wind (15 km s −1 ) indicate a time scale of ≈6500 yr.…”
Section: Chemistrysupporting
confidence: 50%
“…While common in the envelopes of young stars, methanol is very rare around more evolved stars, having been reported to date towards only three other systems, all in a post-MS phase: the binary system HD 101584 in a common envelope phase with an A6Ia primary that terminated as a postasymptotic giant branch (post-AGB) or red supergiant star (Olofsson et al 2017(Olofsson et al , 2019; in the bi-polar nebula around the post-AGB Mira-type variable OH231.8+4.2 (Sánchez Contreras et al 2018); and a low-significance detection at extremely low abundance towards the massive yellow hypergiant IRC+10420 (Quintana-Lacaci et al 2016). The detections in η Car indicate conditions favorable to complex molecule formation at the upper extreme of stellar mass and evolutionary end point, as a candidate progenitor of a core collapse supernova of Type II (should the primary explode in its current phase) or Type Ib/c.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling exercises of Wong (2013) found that it was impossible to explain the SiO emission, in particular the radial intensity profiles, with the model of two disconnected gas shells from Castro-Carrizo et al (2007). Indeed, a higher gas density throughout the entire SiO-emitting region is required (Wong 2013;Quintana-Lacaci et al 2016). Therefore, it is speculated that the SiO emission originates from localised clumpy structures, possibly created by shocks, that are not represented by the global mass-loss history as traced by CO emission (Wong 2013, Dinh-V.-Trung et al, in prep.…”
Section: Nh 3 Model Of Irc +10420mentioning
confidence: 99%
“…These O-rich sources towards which Nbearing molecules other than HCN have been detected include OH 231.8+4.2 Sánchez Contreras et al 2015), IRC +10420 (Quintana- Lacaci et al 2013Lacaci et al , 2016, and IK Tau (Velilla Prieto et al 2017). This may suggest that there could be a general enhancement of the production of 14 N from stellar nucleosynthesis (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation